Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 8



Work Step by Step

RECALL: $(f+g)(x) = f(x) + g(x)$ Using the formula above gives: $(f+g)(x) = (-2x+3)+(x^2-5) \\(f+g)(x)= x^2-2x+(3-5) \\(f+g)(x)= x^2-2x+(-2) \\(f+g)(x)= x^2-2x-2$ Thus, to evaluate the given expression, substitute 4 to the equation above to obtain: $f(4) +g(4) \\= (f+g)(4) \\= 4^2-2(4)-2 \\=16-8-2 \\=8-2 \\=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.